Sở hữu nước ngoài và nắm giữ tiền: Bằng chứng phi tuyến từ các công ty thuộc nhóm ngành hàng tiêu dùng tại Việt Nam trước, trong và sau COVID-19 - Hoàng Cẩm, Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The study examines the nonlinear effect of foreign ownership on cash holdings of listed consumer-goods firms in Vietnam, and investigates how this relationship changes before, during, and after the COVID-19 pandemic. Using a sample of 688 firm-year observations from 86 firms over the period 2017‒2024, the results reveal an inverted U-shaped relationship between foreign ownership and cash holdings. Although this relationship persists across all three subperiods, the turning point varies significantly: staying at 28.5% before COVID-19, declining to 11.4% during the pandemic, and rising to 18.2% in the post-pandemic period. The sharp decrease during COVID-19 suggests that firms adjusted their liquidity policies in response to heightened uncertainty. The results highlight the importance of foreign ownership in shaping corporate cash holding decisions and provide implications for both managers and policymakers